2022
DOI: 10.1128/spectrum.01147-22
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis Virus (JEV) NS1′ Enhances the Viral Infection of Dendritic Cells (DCs) and Macrophages in Pig Tonsils

Abstract: Pigs are amplification hosts for Japanese encephalitis virus (JEV). JEV can persist in the tonsils for months despite the presence of neutralizing antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…PRF is utilized by many viruses to increase the coding capacity within a limited viral genome, and the related translation product always benefits virus infection of the host. For example, NS1’, a PRF product of Japanese encephalitis virus, enhanced the viral infection of dendritic cells and macrophages [ 31 ], while the live-attenuated vaccine SA 14 -14–2 strain, which had lost NS1’ expression, showed slower replication kinetics in cells and was essentially non-neuroinvasive and non-neurovirulent in weanling ICR mice [ 32 ]. A transcription factor protein produced by alphaviruses via a -1 PRF played a role in viral assembly, as transcription factor-deficient virus exhibited reduced virion release [ 33 ] and attenuated pathogenesis [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…PRF is utilized by many viruses to increase the coding capacity within a limited viral genome, and the related translation product always benefits virus infection of the host. For example, NS1’, a PRF product of Japanese encephalitis virus, enhanced the viral infection of dendritic cells and macrophages [ 31 ], while the live-attenuated vaccine SA 14 -14–2 strain, which had lost NS1’ expression, showed slower replication kinetics in cells and was essentially non-neuroinvasive and non-neurovirulent in weanling ICR mice [ 32 ]. A transcription factor protein produced by alphaviruses via a -1 PRF played a role in viral assembly, as transcription factor-deficient virus exhibited reduced virion release [ 33 ] and attenuated pathogenesis [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that NS1’ is produced by programmed ribosomal frameshiftthat causes 52 amino acids added to the C-terminus of NS1. NS1′ is commonly associated with flavivirus replication complexes and plays a role in viral neuroinvasiveness ( Melian et al., 2010 ; Xie et al., 2022 ; Young et al., 2013 ). In addition, multiple reports have showed that JEV NS1′ is involved in regulating the host antiviral response ( Li et al., 2021 ).…”
Section: Flavivirus Ns1: a Multifunctional Proteinmentioning
confidence: 99%